2014
DOI: 10.1155/2014/273870
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effect of Egyptian Cape Gooseberry Fruit (Physalis peruvianaL.) against Acute Renal Injury in Rats

Abstract: This study aimed to evaluate the renoprotective effect of Physalis peruviana L. extract (PPE) on acute renal injury in rats. Adult male rats (n = 36) were divided into six groups that were fed with basal diet throughout the experiment (33 days). The first group was normal group, the second and the third groups were administered orally with 100 and 150 mg PPE/kg body weight (BW) respectively, the fourth group was injected intraperitoneally with 5 mg/kg BW cisplatin once on the 28th day to induced ARI, and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 54 publications
0
11
0
3
Order By: Relevance
“…According to the results, the administration of a single dose of Streptozotocin (50 mg/kg weight body) increased water consumption. Other studies have shown that diabetes mellitus is characterized by classical symptoms such as polyphagia, and polydipsia which are exhibited in HFD-STZ diabetic rats and this may be attributed to the impaired glucose homeostasis as a result of insulin inefficiency (Akbarzadeh et al, 2007). Water consumption was inversely related to food intake, this was an indication that the decrease in food intake in diabetic animals was linked to the significant amount of sugars in the blood that had an impact on the index of satiety.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…According to the results, the administration of a single dose of Streptozotocin (50 mg/kg weight body) increased water consumption. Other studies have shown that diabetes mellitus is characterized by classical symptoms such as polyphagia, and polydipsia which are exhibited in HFD-STZ diabetic rats and this may be attributed to the impaired glucose homeostasis as a result of insulin inefficiency (Akbarzadeh et al, 2007). Water consumption was inversely related to food intake, this was an indication that the decrease in food intake in diabetic animals was linked to the significant amount of sugars in the blood that had an impact on the index of satiety.…”
Section: Discussionmentioning
confidence: 90%
“…A phytochemical screening in regeneration plant, callus from seed, leaf and fruits from mother plants of P. peruviana, showed the present of alkaloids, glycosides, cardiac glycosides, saponins, phenol, sterol, tannins, flavonoids and diterpene (Lashin and Elhaw, 2016). A phytochemical investigation of the crude ethanolic extract of P. peruviana L. revealed the presence of phenols, flavonoids, phytosterols, glycosides, sterols, saponins, tannins and alkaloids (Ahmed, 2014). Previous phytochemical studies have isolated a number of compounds from P. peruviana, such as ticloidine, withanolides, phenolics and phytosterols (Gautam et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The consumption of berries has been linked to the prevention of some chronic and degenerative diseases. The term 'berry fruits' encompasses the so-called 'soft fruits', enhanced other antioxidant enzymes in kidney homogenate compared to cisplatin group [15]. The mechanism of the consumption of the berries and their influence on metabolism were not studied.…”
Section: Introductionmentioning
confidence: 99%